The Role of System Thinking in Achieving the SDGs, Agenda 2030 & the Paris Agreement - De Pinto, Alessandro (2017)
Senior Research Fellow, Alex De Pinto's presentation at COP23 - November 2017. Agricultural development must meet multiple challenges